Cloning, expression, and characterization of a thermostable and pH-stable laccase from Klebsiella pneumoniae and its application to dye decolorization. (February 2017) - Liu, Yihan; Huang, Lin; Guo, Wei; Jia, Leibo; Fu, Yu; Gui, Shuang; Lu, Fuping
Graphical abstract: Highlights: A novel laccase from Klebsiella pneumoniae was cloned and the rLac was expressed in Escherichia coli . The rLac was thermostable and pH stable and resistant toward metal ions. The structure–function relationship of rLac under different conditions was analyzed by far-UV CD spectroscopy. The rLac could decolorize tested dyes with high decolorization efficiencies. Abstract: A thermostable and pH-stable laccase from Klebsiella pneumoniae was cloned and expressed in Escherichia coli . The recombinant laccase (rLac) achieved a specific activity of 7.12 U/mg after purification by Ni-affinity chromatography. Optimal enzyme activity was observed at pH 4.0 and 35 °C for 2, 2′-azino-bis (3-ethylbenzthiazoline sulfonic acid) (ABTS) oxidization and pH 8.0 and 70 °C for 2, 6-dimethoxyphenol (2, 6-DMP) oxidization. Thermostability and pH stability studies showed that the rLac was stable over the range of 30–70 °C and pH 5.0–9.0 using 2, 6-DMP as substrate. Circular dichroism analysis suggested that the secondary structure of the rLac mainly consisted of α-helix that played a vital role in maintaining laccase activity and revealed the potential mechanisms for the changes in laccase activity under varying pHs (3.0–11.0) and temperatures (20–90 °C). Finally, the rLac could decolorize the tested dyes with high decolorization efficiency.